National Hockey League Fights per Game and Viewership Trends: 2000-2020 - Thomas A. Fortney; Liana J. Tedesco; Nathan J. Kopydlowski; Jack F. Korzelius; Sohil S. Desai; Charles A. Popkin; Charles A. Popkin (Frontiers Media S.A., 2022)
BackgroundThough once considered an integral part of professional hockey, fighting carries significant health risks to players. Fighting has remained legal in the National Hockey League (NHL) due to its purported economic and entertainment value. However, fights per game have diminished over the past 20 years, challenging the necessity of fighting to promote fan attendance.HypothesisDespite decreasing fighting rates, attendance has been stable and is negatively associated with fights per game.MethodsTwo public databases were reviewed to determine attendance, fighting majors, goals scored, and games played for each NHL team from 2000 to 2020 and averaged on a per game basis. Univariate analysis was used to evaluate relationships between attendance and fights, attendance and goals, as well as goals and fights.ResultsFights per game decreased from a peak of 0.64 in 2002 to a low of 0.18 in 2020, while average attendance increased from a low of 16,549 in 2004 to a peak of 17,768 in 2013, before settling between 17,400 and 17,500 during the final three seasons of the study period. A significant negative correlation was found between attendance and fights per game (R = −0.6617, p = 0.0020). There was a positive, but not significant correlation between attendance and goals per game (R = 0.2457, p = 0.3105). A significant inverse correlation existed between goals per game and fights per game (R = −0.521, p = 0.0222).ConclusionsNHL fighting rates have diminished during the past two decades, while fan attendance has increased. A significant negative correlation exists between fan attendance and fights per game, casting doubt on fighting's entertainment value. Meanwhile, a significant inverse correlation was noted between goals per game and fights per game. Taken together, these findings suggest fans may prefer higher scoring and less violent competitions. We conclude by suggesting that prohibiting fights in the NHL could improve player safety without negatively impacting fan attendance.